2022
DOI: 10.21927/ijubi.v5i2.2604
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis Untuk Review Destinasi Wisata Unggulan Gunung Kidul Menggunakan Metode Lexicon Dan Pivot

Abstract: Social media in providing freedom of access to information has a rapid effect on tourist destinations in Indonesia. A tweet may also contain information or conditions about tourist destinations that they will or have visited, such as visitor experiences in traveling, visitors' opinions of tourist attractions, and other tourist attractions. The condition of tourism globally, especially in the Gunungkidul area after the Covid-19 pandemic, has experienced a significant decline. This condition motivated researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[26] utilizes the Support Vector Machine (SVM) method to identify preferences for goods and services when traveling, using the sentiment approach of travelers visiting Ubud tourism destinations. On the other hand, [27] demonstrates how the branding of popular tourist spots is examined using the lexicon and pivot methodologies. This shows that sentiment analysis methods can be applied with classification algorithms like SVM, NBC, DT, and k-NN that are compatible with the characteristic of the dataset.…”
Section: Figure 5 Number Of Resorts Hotels and Homestay In Raja Ampat...mentioning
confidence: 99%
“…[26] utilizes the Support Vector Machine (SVM) method to identify preferences for goods and services when traveling, using the sentiment approach of travelers visiting Ubud tourism destinations. On the other hand, [27] demonstrates how the branding of popular tourist spots is examined using the lexicon and pivot methodologies. This shows that sentiment analysis methods can be applied with classification algorithms like SVM, NBC, DT, and k-NN that are compatible with the characteristic of the dataset.…”
Section: Figure 5 Number Of Resorts Hotels and Homestay In Raja Ampat...mentioning
confidence: 99%
“…Some of the efforts to digitize tourism in Gunungkidul after the pandemic were carried out with the help of the surrounding community as the main actor of digitization, in the form of utilizing digital marketing through social media and websites for the promotion of Telaga Jonge tourism (Andi Candra et al, 2022), implementing virtual tourism for the climbers of Mount Nglanggeran Ancient Volcano (Sekarsih & Mustopa, 2022), while media literacy, regional mapping, and digital branding of Langse Caves tourism has been considered as an effective promotional strategy (Pudrianisa, 2021). The integration of tourism promotion efforts with the technology and information sector after the pandemic has sparked research interest in collecting data on public sentiment about tourism destinations, where only 1% of comments on Gunungkidul were unfavorable, which is a remarkably good response for a region where tourism is a major industry (Larasati et al, 2022). In a comprehensive study of Gunungkidul potential tourists, Wijaya et al (2022) found that Gunungkidul's tourism spots are primarily visited by young female visitors, students, and employees aged 11 to 25.…”
Section: Introductionmentioning
confidence: 99%